Lexicon development for lip products using descriptive sensory analysis - Dooley, Lauren (Kansas State University, 2007)
The cosmetic industry is growing rapidly, and one popular category is lip products. Women consider lip products a necessity and many would not leave home without it. Though the bigger cosmetic companies may have internal cosmetic lexicons, they are not available in the public domain. The purpose of this study was to develop a lexicon for descriptive sensory testing of lip products. Lip balms, lip glosses, and lipsticks were tested in this study. In part 1 (EXPERIMENT 1), two focus groups were conducted to understand women's perceptions of lip products, and also to elicit desirable and undesirable characteristics in the products. The women's idea of a perfect lip product was: clear/sheer/neutral color, smooth, not sticky, moisturizing and flavorless/tasteless. In part 2 (EXPERIMENT 2), a lexicon was developed for the lip products. Attributes were categorized under "Initial Texture", "Initial Appearance", "After Appearance" and "After Texture." In part 3 (EXPERIMENT 3) of the study, the lexicon was validated by testing various lip products using lexicon developed in part 2. The analysis of variance (ANOVA) results by product type indicated that the lexicon was able to differentiate among the lipsticks, lip balms and lip glosses. The lexicon was further able to show similarities and differences within a product type. Principal component analysis and cluster analysis, which are both multivariate techniques, validated the inferences from the univariate analysis (ANOVA). The two panelist groups (three panelists from the lexicon development panel – group 1, and three new panelists – group 2) showed no differences (P > 0.05) in attribute evaluations for all the samples tested. The lexicon developed in this study could be used to identify similarities and differences in other lip products such as lip plumper, lip liners and multi-use products. The authors hope that this research is extrapolated to other aspects of the personal care industry, such as hair care and skin care, and can aid in product development, product optimization, and claim substantiation.
Keywords: Lexicon development; Lip products; Descriptive analysis; Agriculture, Food Science and Technology (0359)